Separation of Powers in Baron de Montesquieu: Philosophical Appraisal - Agu, Sunny Nzie (PT FORMOSA CENDEKIA GLOBAL, 2024)
In a democratic system, citizens of a given country vote to elect their representatives who will form a government. Fair and equal treatment is required to be provided for every citizen by the government such as fundamental rights, popular and free participation in governance and so on. However it is quite unfortunate that men, once vested with power, abuses it there by causing despair among citizens, just as it is being portrayed in most African countries. Therefore it is necessary that power becomes a check to power. Having seen the need for such check and balances in power, Baron De Montesquieu in his treatise ‘Spirit of Laws’ espoused the separation of powers among the three arms of government in a democratic setting to avoid the abuse of powers.